Sieviešu tēlu transformācija Hellas Vuolijoki lugās - Suhanova, Renāte (Latvijas Universitāte, 2023)
Bakalaura darbā “Sieviešu tēlu transformācija Hellas Vuolijoki lugās” pētītas sieviešu tēlu pārmaiņas igauņu izcelsmes somu rakstnieces sarakstītajās trīs lugās (“Niskavuori sievietes” jeb “Akmens ligzda” (Niskavuoren naiset) (1933), “Niskavuori maize” (Niskavuoren leipä) (1938) un “Niskavuori jaunā saimniece” (Niskavuoren nuori emäntä) (1940)) no “Niskavuori” (Niskavuori) lugu cikla. Darba mērķis ir daiļdarbu sieviešu tēlu izzināšana literārajā un sociālajā kontekstā lugās aprakstītājā laikā, sieviešu lomas atklāšana Somijas vēsturē, kā arī sieviešu balsstiesību un dzimumu līdztiesības kustības ietekme uz sieviešu lomas transformāciju sabiedrībā. Pētāmā problēma ir izmaiņas sieviešu tēla veidošanā laika, vēstures notikumu un darba autora pieredzes ietekmē. Mērķa sasniegšanai tika apskatīta teorētiskā literatūra par feminisma teoriju, kustību par sieviešu tiesībām, kā arī lugu autores biogrāfija. Ņemot vērā saņemto informāciju, trīs galvenie sieviešu tēli tika analizēti un salīdzināti trīs aspektos - attiecības ar vīru, saimnieces loma un attieksme pret laimi. Atslēgvārdi: sieviešu literatūra, feminisms, Hella Vuolijoki, Niskavuori, sieviešu tiesības.

Bachelor’s thesis “Transformation of Female Characters in Hella Wuolijoki's Plays” examines transformation of female characters in three plays written by the Finnish writer of Estonian origin (“Women of Niskavuori” (Niskavuoren naiset) (1933), “Bread of Niskavuori” (Niskavuoren leipä) (1938) and “The Young Mistress Niskavuori” (Niskavuoren nuori emäntä) (1940) from the Niskavuori cycle of plays. The aim of the thesis is to explore the female characters in the plays in their literary and social contexts during the time described in the plays, to reveal the role of women in Finnish history, and the impact of the women's suffrage and gender equality movements on the transformation of women's roles in society. The main problem concerns the change in the image of women as a result of time, historical facts and the experience of the author of the work. To achieve the aim, theoretical literature on feminist theory, the movement for women's rights, as well as the biography of the author of the play were reviewed. In the light of the information received, the three main female characters were analysed and compared in three aspects: the relationship with husband, the role of the housewife and the attitude towards happiness. Keywords: women's literature, feminism, Hella Wuolijoki, Niskavuori, women's rights.
Transformation of Female Characters in Hella Wuolijoki's Plays
Keywords: Valodniecība; sieviešu literatūra; feminisms; Hella Vuolijoki; Niskavuori; sieviešu tiesības